Karakteristik Tes yang Baik dan Proses Penyusunan Instrumen Tes untuk Pembelajaran di Sekolah - Rama Armedi (Educational Consultant & Counseling Career (EC3) Mataram, 2025)
Evaluation in learning aims to see the abilities and understanding of students in accordance with the objectives that have been set. Tests as a data collection tool must show the tendencies that exist in their preparation. This paper discusses the characteristics of a good test and the stages of preparing test instruments with a library research approach. The results of this paper state that the characteristics of a good test are tests that meet requirements such as validity, reliability, objectivity, practicality, and economy. And through the steps of its development, namely by determining objectives, developing instrument specifications, choosing the type of instrument, preparing the type of instrument, and testing the instrument. A good test will provide an overview of what needs to be improved regarding evaluation. And a good test can be a powerful tool to improve education.